Hands-on data science with SQL Server 2017 : perform end-to-end data analysis to gain efficient data insight - Chmel, Marek; Mužný, Vladimír (Packt Publishing, 2018)
Learn how to utilize Microsoft SQL Server with NoSQL concepts for data science challenges. This book will help enhance your knowledge beyond data querying & processing tasks by implementing a data science pipeline. We will implement data science tasks and show how to use them on a day-to-day basis for efficient smart predictive models.